2014
DOI: 10.1002/hed.23655
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal submucosal bevacizumab for epistaxis in hereditary hemorrhagic telangiectasia: A double‐blind, randomized, placebo‐controlled trial

Abstract: Background The purpose of this study was to investigate the efficacy of bevacizumab (“Avastin”) for the treatment of epistaxis in hereditary hemorrhagic telangiectasia (HHT). Methods In this double blind, placebo controlled trial, 15 adult patients with HHT with a minimum of 2 epistaxis episodes per week were randomized. A history of thromboembolic events or recent or planned surgery led to exclusion. Patients received a single intranasal submucosal injection (10 mL) of 100 mg bevacizumab or placebo. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 8 publications
2
102
1
1
Order By: Relevance
“…drugs related to female sex hormones are increased thrombotic events and feminization of men. A fourth double blind placebo controlled study on HHT showed that intranasal submucosal injection of bevacizumab led to an improvement in epistaxis; however, this was not statistically significant [15]. Potential side effects of this antibody against vascular endothelial growth factor (VEGF) include thrombembolic events.…”
Section: Discussionmentioning
confidence: 96%
“…drugs related to female sex hormones are increased thrombotic events and feminization of men. A fourth double blind placebo controlled study on HHT showed that intranasal submucosal injection of bevacizumab led to an improvement in epistaxis; however, this was not statistically significant [15]. Potential side effects of this antibody against vascular endothelial growth factor (VEGF) include thrombembolic events.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 However, data on intranasal bevacizumab have been conflicting, and studies investigating the use of intravenous bevacizumab are limited to case reports and retrospective series. 8 Treatment of HHT involves a multidisciplinary approach of specialists in cardiology, pulmonology, hepatology, interventional radiology, ear, nose and throat (ENT), genetics, and hematology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, serum VEGF is reportedly increased in HHT patients, although levels do not correlate with disease severity [100][101][102]. Administration of Bevacizumab (Avastin Ò ), a VEGF antibody, can ameliorate liver AVMs [103][104][105] and reduce epistaxis [106][107][108][109][110][111][112], although a recent Phase I clinical trial (nasal spray administration) disappointingly showed no efficacy in the treatment of epistaxis [113]. Thalidomide is a second HHT therapeutic that targets angiogenesis.…”
Section: Medical Therapies For Hht: Current Practice and Future Perspmentioning
confidence: 98%